Atributos físicos e químicos do solo sob cultivos de outono-inverno em sistema de semeadura direta - Sereia, Rodrigo César [UNESP] (2014)
The physical and chemical soil attributes go hand in hand, and science seeks to improve the understanding about the interaction of these, aiming to include sustainability through conservation of soil and its natural resources, using the own soil system as a tool to reduce anthropogenic practices. The aim of this study was to evaluate the physical and chemical soil properties under different crops in autumn-winter established five years ago in no-tillage system and clarify the influence of these attributes on the grain yield of soybean crop and its root growth. The experiment was conducted on an Oxisol clay texture. Four treatments autumn-winter, were established, Brachiaria ruziziensis (B), maize (M), maize intercropped with B. ruziziensis (M+B) and cowpea (C) and in summer was grown soybeans. Samplings were carried out during soybean flowering, for the analysis of physics and chemistry, were also taken samples of soybean roots. At the end of the experiment proceeded soybean harvest to determine grain yield. There was a decrease in the macroporosity and an increase in bulk density of the soil in the B treatment compared to the other treatments, due to the animal trampling. The cowpea provided greater water retention in the layers below 0,10 m, due to the smaller influence of roots of this crop and higher microporosity in the soil. The largest Mean Geometric Diameter (MGD) and Mean Weight Diameter (MWD) were observed in treatments B, M, and M+B and the lowest values in C. Treatment B had higher percentage of soil mass distributed in aggregates > 2,0 mm in all layers, while in treatment C there was the lowest aggregate stability (> 2,0 mm) in the layers below 0.10 m. M and M + B had intermediate stability of aggregates between treatments B and C. There was no difference in resistence to penetration (RP) between the treatments, this only varied with depth and was higher in the second and third layer ...